Pengaruh Teknik Reinforcement Terhadap Perilaku Off-Task Behavior Siswa SMK Swasta Kristen BNKP Gunungsitoli - Jernih Jaya Hulu; Jonisman Kristian Laoli (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study used a quantitative approach with quasi-experimental methods with a pre-experimental research design type one group pretest-posttest design. This study aims to determine the effect of reinforcement techniques on the of-task behavior of students of BNKP Gunungsitoli Private Vocational School. This research population is students at Christian Private Vocational School BNKP Gunungsitoli. The sample of the study was class XI-TKJ-1 whose number of students was 19 children. The average result of the pretest was 10.84, after the pretest was carried out then given treatment in the form of using reinforcenment to reduce off-task behavior, during the treatment there was a change, namely the student's off-task behavior decreased which can be seen from the posttest results where the average was 1.16. To test the significance by testing the accepted alternative hypothesis (Ha), it is known that the significance value is 0.00 < 0.05 which means that variable X influences Variable Y, it is stated that there is a change in off-task behavior before and after reinforcement techniques are given.